Modulating Aβ [A-beta] aggregation by tyrosol-based ligands: the crucial role of the catechol moiety - Romanucci, Valeria; García-Viñuales, Sara; Tempra, Carmelo; Bernini, Roberta; Zarrelli, Armando; Lolicato, Fabio; Milardi, Danilo; Di Fabio, Giovanni (Biophysical chemistry, 2020)
The abnormal deposition of Aβ amyloid deposits in the brain is a hallmark of Alzheimer's disease (AD). Based on this evidence, many current therapeutic approaches focus on the development of small molecules halting Aβ aggregation. However, due to the temporary and elusive structures of amyloid assemblies, the rational design of aggregation inhibitors remains a challenging task. Here we combine ThT assays and MD simulations to study Aβ aggregation in the presence of the natural compounds tyrosol (TY), 3-hydroxytyrosol (HDT), and 3-methoxytyrosol (homovanillyl alcohol - HVA). We show that albeit HDT is a potent inhibitor of amyloid growth, TY and HVA catalyze fibril formation. An inspection of MD simulations trajectories revealed that the different effects of these three molecules on Aβ1-40 aggregation are ascribable to their capacity to arrange H-bonds network between the ligand (position C-3) and the peptide (Glu22). We believe that our results may contribute to the design of more effective and safe small molecules able to contrast pathogenic amyloid aggregation
Gesehen am 21.12.2020